2018
DOI: 10.1111/echo.14208
|View full text |Cite
|
Sign up to set email alerts
|

Trends in use of echocardiography in hospitalized patients with syncope

Abstract: Purpose We sought to assess the trends in use, predictors of echocardiography, and its impact on in‐hospital mortality in patients admitted with syncope using a large national database. Methods Utilizing the Nationwide Inpatient Sample (NIS) database from 2001 to 2014, we identified adult patients (>18 years) with a primary discharge diagnosis of syncope and use of echocardiogram was ascertained. Results A total of 3 174 619 patients with a primary discharge diagnosis of syncope were identified, of which 184 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In another study, Satish et al. reported that, 3 174 619 patients with syncope were evaluated, and the performing of echocardiography did not effect the in‐hospital mortality rates ( p = .155), but was related with a 14.6% rise in length of hospitalization and a 22.6 % in‐hospital cost compared the not using of echocardiography ( p < .001, p < .001, respectively) 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Satish et al. reported that, 3 174 619 patients with syncope were evaluated, and the performing of echocardiography did not effect the in‐hospital mortality rates ( p = .155), but was related with a 14.6% rise in length of hospitalization and a 22.6 % in‐hospital cost compared the not using of echocardiography ( p < .001, p < .001, respectively) 19 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the high mean age of this group may have caused to the more echocardiographic abnormalities.In this study, no possible TTE findings were determined to explain this complaint in the group with recurrent syncope attacks. As possible causes included severe aortic or mitral valve disorder, severe LV dilatacost compared the not using of echocardiography (p < .001, p < .001, respectively) 19. The American Heart Association and European Society of Cardiology recommend echocardiography in patients with syncope only if the patient's history or examination suggests a cardiac etiology or if the baseline ECG is abnormal 20,21.…”
mentioning
confidence: 99%